Sejarah Pergulatan Politik Hukum Islam di Indonesia - Sirajuddin M. (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2016)
This study focuses to the development and the existence of Islamic law and political law relationship in Indonesia. The purpose of this study is to examine Islamic law in the legal system and institutions in Indonesia. The method of this study is the legal political studies with E. Betti historical-hermeneutical approach. The result of this study indicates that by borrowing the study of E. Betti hermeneutic, it can be revealed that the contribution of norms of Islamic law in a legal system, namely what is true in the past can still exist and allow it to become a basic foundation in the development of subsequent law. Therefore, the development of national law cannot deny the historical role of Islamic legal norms that has given its own color to the community. In the context of Indonesia, the relationship between Islamic law and law policies is closely related as one, because the norms of Islamic law have become a source of national laws. The history shows that since the era of the Islamic kingdoms in the Indonesian Archipelago, the era of independence, and up to the era of reform, the norms of Islamic law remain becoming a source of Indonesian material laws, and they affect and color the character of national law development. Institutionalization of Islamic norms in the construction of national law is constitutional, because it acts in accordance with the soul and the spirit of Pancasila and the Indonesian Constitution.